A rare case of twin fetal papyraceous in triplet pregnancy: clinical challenges and insights - Agarwal, Mamta; Jindal, Saurabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The occurrence of twin papyraceous foetuses in triplet pregnancy is rare. A papyraceous foetus is found almost exclusively in multiple gestation. Twin fetal papyraceous occurs when one or more fetuses die in utero with retention of the fetus for a minimum of 10 weeks resulting in mechanical compression of the small fetus and loss of fluid such that it resembles parchment paper. This condition can have serious implications for the remaining fetuses and the overall pregnancy. Understanding the causes, potential complications, and management strategies for triplet pregnancies complicated by twin fetal papyraceous is crucial for ensuring the best possible outcomes for both mother and babies. We report here a case of a 24 year female with triplet pregnancy with two foetus papyracei who delivered a healthy baby at 34 weeks.